Thermal management with and without servo-controlled system in preterm infants immediately after birth: a multicentre, randomised controlled study. Issue 6 (17th February 2021) - Cavallin, Francesco; Doglioni, Nicoletta; Allodi, Alessandra; Battajon, Nadia; Vedovato, Stefania; Capasso, Letizia; Gitto, Eloisa; Laforgia, Nicola; Paviotti, Giulia; Capretti, Maria Grazia; Gizzi, Camilla; Villani, Paolo Ernesto; et al.
Abstract : Background: The thermal servo-controlled systems are routinely used in neonatal intensive care units (NICUs) to accurately manage patient temperature, but their role during the immediate postnatal phase has not been previously assessed. Objective: To compare two modalities of thermal management (with and without the use of a servo-controlled system) immediately after birth. Study design and setting: Multicentre, unblinded, randomised trial conducted 15 Italian tertiary hospitals. Participants: Infants with estimated birth weight <1500 g and/or gestational age <30 +6 weeks. Intervention: Thermal management with or without a thermal servo-controlled system during stabilisation in the delivery room. Primary outcome: Proportion of normothermia at NICU admission (axillary temperature 36.5°C–37.5°C). Results: At NICU admission, normothermia was achieved in 89/225 neonates (39.6%) with the thermal servo-controlled system and 95/225 neonates (42.2%) without the thermal servo-controlled system (risk ratio 0.94, 95% CI 0.75 to 1.17). Thermal servo-controlled system was associated with increased mild hypothermia (36°C–36.4°C) (risk ratio 1.48, 95% CI 1.09 to 2.01). Conclusions: In very low birthweight infants, thermal management with the servo-controlled system conferred no advantage in maintaining normothermia at NICU admission, while it was associated with increased mild hypothermia. Thermal management of preterm infants immediately after birth remains a challenge. Trial registration number: NCT03844204